2006
DOI: 10.1080/09583150500532535
|View full text |Cite
|
Sign up to set email alerts
|

Prey selection byDicyphus hesperusof infected or parasitized greenhouse whitefly

Abstract: The development of effective biological control programs in which predators are integrated with other natural enemies such as parasitoids and entomopathogens requires an understanding of their interactions. In this study we examined the extent to which the omnivorous mirid bug Dicyphus hesperus , an effective biological control agent of greenhouse whiteflies, accepts prey that are either parasitized by the specialist whitefly parasitoid, Encarsia formosa or infected by the generalist fungal entomopathogen, Bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Most studies have examined small coccinellid predators (Delphastus and Serangium ) and have shown that predation on young parasitoids is indiscriminant, but that because of physical factors associated with parasitoid development, older larval and pupal parasitoids are avoided by these beetles (Heinz et al 1994;Hoelmer et al 1994;Al-Zyoud & Sengonca 2004;Fazal & Xiang 2004). The mirid predator Dicyphus hesperus Knight, similar in size to G. punctipes , was found to be an indiscriminant IG predator of Encarsia formosa Gahan pupae in greenhouse whiteflies (McGregor & Gillespie 2005) and this behavior was not altered by parasitoid age (Labbe et al 2006). No effect of parasitoid age was observed here either, because all three predators readily attacked both larval and pupal stage parasitoids.…”
Section: Intraguild Predation On Eretmocerus 615mentioning
confidence: 76%
“…Most studies have examined small coccinellid predators (Delphastus and Serangium ) and have shown that predation on young parasitoids is indiscriminant, but that because of physical factors associated with parasitoid development, older larval and pupal parasitoids are avoided by these beetles (Heinz et al 1994;Hoelmer et al 1994;Al-Zyoud & Sengonca 2004;Fazal & Xiang 2004). The mirid predator Dicyphus hesperus Knight, similar in size to G. punctipes , was found to be an indiscriminant IG predator of Encarsia formosa Gahan pupae in greenhouse whiteflies (McGregor & Gillespie 2005) and this behavior was not altered by parasitoid age (Labbe et al 2006). No effect of parasitoid age was observed here either, because all three predators readily attacked both larval and pupal stage parasitoids.…”
Section: Intraguild Predation On Eretmocerus 615mentioning
confidence: 76%
“…Subject to sufficiently high temperatures to enable mobility, all life cycle stages, whether fed or non-fed, diapausing or non-diapausing, survived for periods of time that would allow them to seek periodic refuge and food in glasshouses that continue production through winter. In this respect, recent studies have shown D. hesperus females feed on Encarsia formosa (Hymenoptera: Aphelinidae) larvae and pupae (parasitoid used as a control agent against T. vaporariorum) in laboratory and glasshouse trials (Labbe et al 2006;McGregor and Gillespie 2005).…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence and ecological consequences of IGP have usually been stud-ied in Petri dishes (e.g. Lucas et al 1997;Burgio et al 2002;Labbé et al 2006), or field cage experiments (e.g. Rosenheim et al 1993;Hoogendoorn & Heimpel 2004;Gardiner & Landis 2007;Chacó n et al 2008).…”
Section: Introductionmentioning
confidence: 99%